PENGUATAN MANAJEMEN PENDIDIKAN BERBASIS INOVASI LOKAL DAN KOLABORASI MULTIPIHAK DI SEKOLAH TERPENCIL - Andika Aprilianto aprilianto (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The quality gap between urban and rural schools in Indonesia extends beyond infrastructure to encompass fundamental dimensions: weak innovation capacity, low community participation, and the absence of collaborative ecosystems among education stakeholders. This article reports the outcomes of a community service program (PKM) conducted at SDN 3 Toyomarto, Singosari, Malang, a primary school situated within the Wonosari Tea Plantation area of PTPN 12 that has undergone a remarkable transformation over the past three years. The program was designed around three core interventions: (1) building a quality culture through Total Quality Management (TQM), (2) participatory analysis of rural education dynamics and challenges, and (3) introduction of the Si Lipan model (Sistem Lumbung Inovasi Pendidikan/Education Innovation Barn System) as a locally-grounded innovation framework. Employing a participatory action approach, the program engaged 50 multi-stakeholder participants and was evaluated through a structured questionnaire with a 72% response rate (n=36). Results demonstrate significant outcomes: an overall satisfaction rate of 96%, with 80.6% of participants grasping the collaborative essence of rural education innovation and 69.4% expressing concrete commitment to initiating innovations in their own schools. These findings affirm that sustainable educational innovation in remote areas is not contingent on resource magnitude, but on leadership quality, the strength of multi-stakeholder collaborative ecosystems, and contextual alignment with local potential.